PENGARUH AIR REBUSAN CENGKEH (SYZYGIUM AROMATICUM) UNTUK MENGURANGI FREKUENSI MUAL DAN MUNTAH PADA IBU HAMIL TRIMESTER AWAL DI KLINIK MURNIATI - Adelia Putri; Atika Pohan (Fakultas Ilmu Kesehatan, 2023)
Pregnancy is a physiological part of a womwns life. Pregnancy is often accompanied by an unpleasant feeling, discomfort that is often felt by pregnant woman, especially in the first trimester, in the form of nausea and vomiting (Voming during pregnancy). The research objective : To find out the effect of giving clove boiled water (syzygium aromaticum) on reducing the frequency of nausea and vomiting in early trimester pregnant women at Murniati clinic in 2023. Methode this study used a quantitative method with a one grup post test desain. The Population of this study included 30 first trimester pregnant women who experianced nausea and vomiting. The sampling technique used is random sampling. Statistical analisis with wicolxon test. Result data analisis obtiment p=0,000 (p<0,05) so that the hipotesis was accepted. This shows that giving clove boiled watwer is effective in reducing the intencity of nausea and vomiting in early trimester pregnant womwn at the Murniati Clinic in 2023. Conclusion there is an effect of giving boiled water with cloves in reducing the frequency of nausea and vomiting in early trimester pregnant women. Keyword : Nausea and vomiting, clove decoction, pregnant women